Refractory cor pulmonale under extracorporeal membrane oxygenation for acute respiratory distress syndrome: the role of conversion to veno-pulmonary arterial assist—a case series - Bagate, François; Masi, Paul; Boukantar, Madjid; Radu, Costin; Saiydoun, Gabriel; Fiore, Antonio; Chiaroni, Paul-Matthieu; Teiger, Emmanuel; Folliguet, Thierry; Gallet, Romain; Mekontso Dessap, Armand (Frontiers in Medicine, 2024)
Introduction: Pulmonary vascular dysfunction during severe acute respiratory distress syndrome (ARDS) may lead to right ventricle (RV) dysfunction and acute cor pulmonale (ACP). The occurrence/persistence of ACP despite conventional extracorporeal membrane oxygenation (ECMO) is a challenging situation. We explored the usefulness of a specific dual-lumen cannula that bypasses the RV, and on which a veno-pulmonary arterial assist (V-P ECMO) was mounted, in ARDS patients.We report a case-series of ARDS patients put on conventional veno-arterial or veno-venous ECMO and presented refractory ACP as an indication for a reconfiguration to V-P ECMO using the ProtekDuo cannula. The primary endpoint was the mitigation of RV and pulmonary vascular dysfunction as assessed by the change in end-diastolic RV/left ventricle (LV) surface ratio.Results: Six patients had their conventional ECMO reconfigured to V-P ECMO to treat refractory ACP. There was a decrease in end-diastolic RV/LV surface ratio, as well as end-systolic LV eccentricity index, and lactatemia immediately after V-P ECMO initiation. The resolution of refractory ACP was immediately achieved in four of our six (66%) patients. The V-P ECMO was weaned after a median of 26 [8-93] days after implantation. All but one patient were discharged home. We detected one case of severe hemolysis with V-P ECMO and two suspected cases of right-sided infective endocarditis.Conclusions: V-P ECMO is useful to mitigate RV overload and to improve hemodynamics in case of refractory ACP despite conventional ECMO.